Relationship between social determinants of health and cognitive performance in an older American population: a cross-sectional NHANES study - Zhen-Guo Yang; Xu Sun; Xue Han; Xiao Wang; Lei Wang (BMC Geriatrics)
Abstract Objective This study aims to investigate the influence of social determinants of health (SDoH) on cognitive performance. Methods This study surveyed a sample of older adults aged 60 years and older from the 2011–2014 cohort of participants in the U.S. National Health and Nutrition Examination Survey (NHANES). Data were collected during each survey cycle on self-reported domains of SDoH, which included eight subscales: employment, family income-to-poverty ratio, food security, education level, health insurance coverage, type of health insurance, home ownership, and marital status. Cognitive performance was evaluated using three tests: the Digit Symbol Substitution Test (DSST) for processing speed, the Animal Fluency Test (AFT) for executive function, and a subtest from the Coalition to Establish an Alzheimer’s Disease Registry (CERAD) for memory. Multifactorial linear regression modeling was employed to explore the association between SDoH and cognitive performance. Results A total of 2,819 elderly subjects were included in this study for analysis, with a mean age of 69.14 ± 0.19 years, 54.36% female and 45.64% male. The study found a negative association between the accumulation of unfavorable SDoH factors and cognitive performance. Similarly, certain unfavorable SDoH domains were negatively associated with cognitive performance. Conclusion The findings suggest that unfavorable SDoH domains, particularly when unfavorable SDoH factors accumulate, are linked to decreased cognitive performance. Actively investigating the relationship between these factors may be a crucial strategy for delaying dementia onset.